2015
DOI: 10.1111/febs.13401
|View full text |Cite
|
Sign up to set email alerts
|

The loop structure of Actinomycete glycoside hydrolase family 5 mannanases governs substrate recognition

Abstract: Endo-β-1,4-mannanases from Streptomyces thermolilacinus (StMan) and Thermobifida fusca (TfMan) demonstrated different substrate specificities. StMan hydrolyzed galactosylmannooligosaccharide (GGM5; 6(III) ,6(IV) -α-d-galactosyl mannopentaose) to GGM3 and M2, whereas TfMan hydrolyzed GGM5 to GGM4 and M1. To determine the region involved in the substrate specificity, we constructed chimeric enzymes of StMan and TfMan and evaluated their substrate specificities. Moreover, the crystal structure of the catalytic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…A, open circle) . The amino acid sequences in loop7 differed between StMan and these mannanases; however, the sequences were well conserved in SlMan, StManII and TfMan . There mannanases did not form a hydrogen bond between loop6 and loop7 because the residue at the position of Ser247 in loop6 of StMan was Gly in these mannanases (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…A, open circle) . The amino acid sequences in loop7 differed between StMan and these mannanases; however, the sequences were well conserved in SlMan, StManII and TfMan . There mannanases did not form a hydrogen bond between loop6 and loop7 because the residue at the position of Ser247 in loop6 of StMan was Gly in these mannanases (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Although mutation analysis showed that the loss of the hydrogen bond did not affect the binding of Ca 2+ to the mutants, it led to a decrease in the eTS. Loop7 of StMandC was positioned for a tight interaction with the substrate compared to its location in the crystal structure without substrate . Asp279, Gln280 and Trp281 in loop7 showed high B‐factors, which exhibited high flexibility and low thermal stability .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The abundance of GH5 increased along with the increase of Streptococcus and Prevotella, GH5 was mainly annotated as endo-glucanase, which is the main ingredient of cellulase [40]. and it also involved in the hydrolysis of galactose, some loops in GH5 enzymes could recognize galactosyl unit [41]. The abundance of GH16 increased along with the increase of Streptococcus and Mesorhizobium, and the degradation of galactose was predicted could be initiated by GH16 [42], this galactanases had substrate speci city acting on galactooligosaccharides [43].…”
Section: Discussionmentioning
confidence: 99%